Cellular Immunotherapy and Locoregional Administration of CAR T-Cells in Malignant Pleural Mesothelioma - Belderbos, Robert A.; Vroman, Heleen; Aerts, Joachim G. J. V. (Frontiers in Oncology, 2020)
Malignant pleural mesothelioma (MPM) is a treatment recalcitrant tumor with a poor overall survival (OS). Current approved treatment consists of first line chemotherapy that only modestly increases OS, illustrating the desperate need for other treatment options in MPM. Unfortunately, clinical studies that investigate the effectivity of checkpoint inhibitor (CI) treatment failed to improve clinical outcome over current applied therapies. In general, MPM is characterized as an immunological cold tumor with low T-cell infiltration, which could explain the disappointing results of clinical trials investigating CI treatment in MPM. Currently, many other therapeutic approaches, such as cellular therapies and cancer vaccines are investigated that could induce a tumor-specific immune response and increase of the number of tumor-infiltrating lymphocytes. In this review we will discuss these novel treatment approaches for MPM.